Family business management - Basco, Rodrigo (Abingdon, Oxon New York, NY Routledge, 2024)
"Family Business Management provides an accessible overview of the core aspects of family business, with an international, practice-based perspective. Structured in four parts, the book covers key topics such as family firm goals, conflict management, human resources, strategy, financial management, family and business governance, and succession planning. A wide variety of cases and examples are used throughout the book to highlight cultural and institutional differences between family businesses in contrasting contexts. Each chapter offers a detailed case study and boxed examples, illustrating real-life family business situations and stimulating students' critical thinking and decision-making. Readers are further supported by learning objectives, discussion questions and further reading suggestions. Digital supplements for instructors include lecture slides, a test bank, additional case studies and exercises, plus animated topic videos and video interviews with academics and family business practitioners. This textbook is the ideal companion for undergraduate and postgraduate family business courses and will also be valuable reading for people working in family businesses"--
Includes bibliographical references and index.
Keywords: Family-owned business enterprises -- Management